Penggunaan inovasi teknologi dalam perawatan di ruang intensif care unit: A literatur review - Mufimah, Mufimah; Monica, Rica; Firmansyah, Dedy; Kamaluddin, Ridlwan (Program Studi Ilmu Keperawatan-fakultas Ilmu Kesehatan Universitas Malahayati, 2025)
Background: Although the development of technology in health care in Indonesia has progressed, the application of technology in the ICU is still relatively limited. According to the Indonesian Ministry of Health (2024), several large hospitals in Jakarta and other big cities have implemented electronic-based patient data management systems and remote monitoring. However, it cannot be denied that there are still many hospitals in the regions that have not utilized technology optimally. Purpose: To analyze the use of technological innovation in intensive care unit care. Method:This research is a literature study with the PRISMA approach. Systematic review using PICO. The search databases used were PubMed/NCBI, Scopus and Sciencedirect with the keywords Innovation AND Technology AND Intensive Care Unit. Results: The types of technological innovations used in intensive care unit care are educational multimedia tools designed to improve ICU nurses' compliance with infection prevention and control practices, an intensive care telemedicine (tele-ICU) program called ERIC (Enhanced Recovery after Intensive Care), Ultrasonic technique Combination of Out-of-Plane Orientation and In-Plane Guidance for radial artery cannulation especially in shock patients in ICU, Virtual Reality (VR) to support the development of clinical decision-making skills, Remotely Tele-mentored Ultrasound (RTMUS) telemedicine to perform ultrasonography remotely. And each type of innovation technology used is significantly influential or effective according to the dependent variable measured. Conclusion: The use of technological innovation in intensive care unit care has been proven to provide benefits in all aspects, starting from infection prevention, quality indicators, and decision making. Keywords: Innovation; Intensif Care Unit (ICU); Technology. Pendahuluan: Perkembangan teknologi dalam perawatan kesehatan di Indonesia telah mengalami kemajuan, namun penerapan teknologi di ICU masih tergolong terbatas. Menurut Kemenkes RI (2024), beberapa rumah sakit besar di Jakarta dan kota-kota besar lainnya telah menerapkan sistem manajemen data pasien berbasis elektronik dan pemantauan jarak jauh. Namun tak dapat dipungkiri masih banyak rumah sakit di daerah yang belum memanfaatkan teknologi dengan optimal. Tujuan: Untuk menganalisis penggunaan inovasi teknologi dalam perawatan di ruang intensif care unit. Metode: Penelitian literatur review dengan pendekatan Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) dan menggunakan PICO. Database pencarian yang digunakan adalah pubmed/NCBI, Scopus,dan Sciencedirect dengan kata kunci